1999
DOI: 10.1016/s0960-9822(99)80261-9
|View full text |Cite
|
Sign up to set email alerts
|

Wound-induced assembly and closure of an actomyosin purse string in Xenopus oocytes

Abstract: We conclude the following: actomyosin purse strings can close single-cell wounds; myosin-II is recruited to wound borders independently of F-actin; purse-string assembly is dependent on a Rho GTPase; and purse-string assembly and closure are controlled by microtubules. More generally, the results indicate that actomyosin purse strings have been co-opted through evolution to dispatch a broad variety of single-cell and multicellular processes, including wound healing, cytokinesis and morphogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
230
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 200 publications
(239 citation statements)
references
References 36 publications
8
230
1
Order By: Relevance
“…(16) The actomyosin array segregates over time: while F-actin assembles throughout the wound array, myosin-2 becomes enriched on the interior circumference. (17) Subsequent studies showed that Rho GTPases direct the actomyosin response during wound healing and are likely responsible for the observed segregation of the actomyosin array. That is, wounding elicits simultaneous local activation of both Rho and Cdc42 about 20 seconds after wounding followed by segregation of active Rho and Cdc42 into complementary zones, with active Cdc42 circumscribing active Rho (Fig.…”
Section: Rho Gtpase Activity Zonesmentioning
confidence: 99%
See 1 more Smart Citation
“…(16) The actomyosin array segregates over time: while F-actin assembles throughout the wound array, myosin-2 becomes enriched on the interior circumference. (17) Subsequent studies showed that Rho GTPases direct the actomyosin response during wound healing and are likely responsible for the observed segregation of the actomyosin array. That is, wounding elicits simultaneous local activation of both Rho and Cdc42 about 20 seconds after wounding followed by segregation of active Rho and Cdc42 into complementary zones, with active Cdc42 circumscribing active Rho (Fig.…”
Section: Rho Gtpase Activity Zonesmentioning
confidence: 99%
“…During oocyte wound healing, for example, myosin-2 concentrates on the interior of the actomyosin array, while dynamic actin is concentrated around the outside of the array. (16,17) That this segregation results from the segregation of the Cdc42 and Rho activity zones is indicated both by the timing of segregation and the effects of experimentally broadening the Rho zone. (3) This raises a further question, namely, why segregate different components of the contractile array?…”
Section: Contributions Of the Zones To Contractile Arraysmentioning
confidence: 99%
“…Such an actin cable has been reported to play a role in the morphogenesis and wound healing of Drosophila embryos (Young et al 1993, Wood et al 2002, in injured singlecelled Xenopus oocytes (Bement et al 1999), in the healing of chick embryo epidermises (Martin & Lewis 1992) as well as in the repair of tissue culture wounds (Bement et al 1993, Altan & Fenteany 2004. It has been suggested that the actin cable functions as a "purse string" contracting the wound edges together (reviewed by Kiehart 1999).…”
Section: Imaginal Disc Wound Healingmentioning
confidence: 99%
“…Membrane resealing is a conserved process by which cells are able to survive mechanical disruption of the plasma membrane (14)(15)(16)(17)(18)(19). Dysferlin-null skeletal and cardiac muscle show enhanced uptake of membrane impermeable dye following laser-induced wounding, suggesting that dysferlin may play a role in membrane resealing (3,20).…”
Section: Introductionmentioning
confidence: 99%